DIVERTICULOSIS IN AMBULATORY PATIENT - Ana Maria Miulescu; Alexandru Ispas (Romanian Medical Journal, 2019)
The aim of this study was to observe the clinical presentation and to descibe same clinical, endoscopic and prognosis aspects for outgoing patients with diverticulosis from Argeş area. Material and method. 192 patients were included in this study, with no prior medical records attesting the presence of diverticulosis. The study was conducted between 2011 and 2015 in ambulatory setting. Medical history, clinical exam and colonoscopy were undertaken during the visit. Inclusion criteria was the diagnosis of diverticulosis. Results. Colonoscopy was the method of investigation for confirmation of diverticulosis. Sex distribution was almost equal, for diverticulitis the sex ratio was raised towards female sex. Most patients were asymptomatic and from urban environment. Hemorrhoids were the cause for most of the hematochezia cases, only one case of diverticular bleeding. Discussions. the outgoing patients have mild symptoms and good clinical status compared to those needing hospitalisation. Differential diagnosis with irritable bowel syndrome needs a careful anamnesis. Conclusions. Frequent location of the diverticula was in the sigmoid and descending colon. Most patients have no symptoms and the number is slightly smaller compared with other studies, but they represent the majority in the analysed group. Most of the diverticulitis patients were older than 66 and females. There is an association between diverticular disease and irritable bowel syndrome